Superbugs: a constraint to achieving the sustainable development goals - Shahriar Mohsin; Mohammad Nurul Amin (Bulletin of the National Research Centre, 2023)
Abstract Background Antimicrobial resistance has already emerged as a major concern not only for public health but also for global economy. It causes a multifaceted crisis in development and growth by increasing the number of infections and deaths. Sustainable Development Goals are in place to ensure that development and growth are continual, as well as to end poverty, protect the environment, and promote peace and prosperity. In this review we tried to highlight the reasons for the prevalence of superbugs as well as their multifaceted impact on healthcare, and demonstrate potential ways to combat them and incorporate them into international policymaking processes. Main body of the abstract The literature review included articles from MEDLINE, EMBASE, Scopus, and PubMed published till the end of the year 2022 using keyword searches. Two hundred and forty-three research articles, review papers and studies written in English language evaluating the impact of Antimicrobial resistance (AMR) on patient, society and economy published until end of the year 2022 were included. Short conclusion This review highlighted the significant impact of antimicrobial resistance (AMR) on the Sustainable Development Goals (SDGs) and was able to identify at least five SDGs that are linked to healthcare. The emergence of superbugs results in increased expenditure, which has serious consequences for the global economy, particularly in developing countries where infectious diseases are prevalent. The overuse and misuse of antibiotics, as well as poor infection control practices, are identified as primary drivers of superbug emergence. However, implementing strategies such as rational antibiotic use, effective infection control practices, and developing new antibiotics and alternative therapies can mitigate the adverse effects of AMR and contribute to achieving the SDGs. It is essential to integrate AMR strategies into national development plans and improve cross-sectoral collaboration among stakeholders to combat superbugs effectively.